Transnacionalização das relações de trabalho: o caso da maquila estadunidense Johnson Controls (plantas FINSA e interiores) e o papel da Federação Internacional de Trabalhadores das Indústrias Metalúrgicas (FITIM) - Espósito, Katiuscia Moreno Galhera [UNESP] (2012)
The internationalization of the companies has been strengthened from the 1970s. Throughout this process, in the ―post-fordist‖ or ―flexible accumulation‖ era, the production chains of multinational companies have become increasingly decentralized, intensifying the international division of labor. Thus, for example, workers in Pakistan, facing low wages and an environment unfavorable to unionization, contribute, although unintentionally, to increase income inequality in the world. The labor unions, in turn, have witnessed the general fall of unionization rates and the deregulation of labor, which have affected even the rights historically won by workers in countries where the social dialogue is considered advanced, like Germany. After all, it is not interesting to the companies the use of manpower with the high costs of German social security, when Pakistani workers can do the same job at a lower cost. One strategy of unions in the face of these processes is to operate at a transnational level, through global networks of information, communication and mobilization. The objective is to apprehend these new forms of labor organization which act transnationally: the Global Union Federations (GUFs). More specifically, this study will examine the internationalization of the campaign of Mexican workers in two production plants (FINSA and Interiores) of a North American maquila, Johnson Controls, and the role of the International Metalworkers‘ Federation (IMF) in this process. We will examine case studies under the light of the literature related to critical theory, transnational unionism, post-fordism/flexible accumulation, social networks and the role of the state. We intend to demonstrate the action of the international networks of trade unions and their results in the two proposed loci.